ADVANTAGES OF USING VIRTUAL LABORATORY PROGRAMS IN PHYSICS - Ajimurat Jumamuratov; Kalilaev Farxad Kobeysinovich (Zien Journals, 2021)
The purpose of preparing students to meet the requirements of the modern world, to teach undergraduate students the basics of physics, is to develop in them a modern scientific and technical outlook. It should be noted that the teaching of physics in higher education is closely linked with higher mathematics, computer science, information technology, the theory of electrical circuits, radio electronics, microelectronics and other disciplines.
Keywords: microelectronics; students; modern; undergraduate